Avaliação dos aspectos psicossociais em pacientes com desordens temporomandibular de origem muscular, articular e mista por meio dos critérios de diagnóstico para pesquisa de DTM ( RDC/TMD) - Teixeira, Nilda Maria (2009)
Temporomandibular disorders (TMD) is a collective term embracing a number of clinical problems that involve the masticatory musculature, the temporomandibular joints (TMJ), or both. The most frequently sign at presentation is pain, usually localized in the muscles of mastication, the preauricular area, and/or the TMJ. Patients with TMD often have limited or asymmetric mandibular movements and joint sounds that are commonly described as clicking, pop-ping, grating, or crepitus. Studies indicate that TMD is a chronic pain condition that shares the major characteristic of other common chronic pain conditions. It is widely recognized that psychological factors may be involved in the pain perception process. Although the etiology of TMD has not been established, psychological factors have been implicated in the predisposition, initiation, and perpetuation of TMD and psychological therapies have been found to be beneficial for some TMD patients. The importance of psychosocial issues was recently highlighted in the development of the Research Diagnostic Criteria for Tempomandibular Disorders (RDC/TMD). Dworkin and LeResche recommend that, in addition to the physical diagnosis (Axis I), a psychosocial assessment of TMD patients be codified on Axis II. Axis II involves the psychosocial impact of chronic pain, characteristic pain intensity, and disability attributed to TMD pain. This emphasis on the importance of psychological issues is reflected in the findings of several studies of TMD patients. The objective of this study was to identify differences between 3 groups of TMD patients, those with muscle problems, articular problems, or both and compare these differences on psychosocial domains. The RDC/TMD data for Axes I and II for 116 patients with a history of TMD, and after was compared the level of depression, somatization and chronic pain grade in patients in single and multiple RDC/TMD diagnostic group. Within the limitations of this study, concluded that female and patients diagnosed with muscle and articular problems was more prevalent, with higher levels of chronic pain grade, tends to show more somatization, and patients diagnosed with articular problems with lower levels of chronic pain grade and Depression.